«Israelita ma di eccezione» Ebrei perseguitati nell'università italiana - Turi, Gabriele (Biblioteca di storia, 2021)
1938 in Italy is marked by the introduction of the racial laws which ejected Jews from schools and universities, preceding similar measures in Germany. The aim of the author is to illustrate the debates in parliament around the Day of Memory and on holocaust denial before dealing with the events of 1938, in order to underline their contemporary significance and to interpret them as linked and not separable. After showing the progress that has been made in terms of historical research and the difficulties that the political world has experienced in taking this work into account, the volume examines the losses in qualitative terms in Italian university teaching and the huge difficulties encountered by professors who had lost their posts and struggled to return to their former positions. The case of Florence is studied closely within the framework of the transformations to university institutions which took place during the Fascist period. The indifference or the silence of the intellectuals, including Gentile, is underlined.